Batia Suter. (Amsterdam : NEROC VGM Amsterdam Roma Publications Amsterdam, 2003)
Book with mainly billboards in which the advertising surfaces display switches, buttons and daily objects. This book (100 signed and bound copies) is a special edition of the publication 'Batia Suter / A meeting outdoors', produced by KesselsKramer and originally published by NEROC'VGM b.v. Amsterdam.
korte biog. [1 p.]
Engels
boek
Keywords: Süter, Batia